Diseases of Salivary Glands: Review - Alhan D Al-Moula (University of Mosul, College of Dentistry, 2010)
The oral cavity is a moist environment, a film of fluid called saliva constantly coats its inner surfaces and occupies the space between the lining oral mucosa and the teeth. Saliva is a complex fluid, pro-duced by the salivary glands, whose important role is maintaining the wellbeing of the mouth. Patients with a deficiency of salivary secretion experience difficulty eating, speaking, swallowing as well as become prone to mucosal infections and rampant caries. In human there are three pairs of major encap-sulated salivary glands - (parotid, submandibular, and sublingual). Located outside the oral cavity, with extended duct systems to discharge their secretion. There are also a multitude of smaller minor unen-capsulated salivary glands. (labial, lingual, palatal, buccal, glossopalatine and retromolar). Located just below and within the mucous membranes, characterized by short duct systems. Secretion of each major salivary gland is not the same, the parotid glands secrete a rich amylase (watery serous saliva), whereas the submandibular gland produces mucinous saliva, and the sublingual gland produces viscous saliva. Because of these variations, saliva found in the mouth is referred to as mixed secretions, as many pro-teins are rapidly removed as they adhere to hydroxyl apatite of teeth and to the oral mucosal surfaces. Diseases of the salivary glands usually bring about changes in the rate of salivary secretion and compo-sition. These changes have a secondary effect in that they lead to the formation of a plaque and calcu-lus, which in turn has a direct bearing on the initiation of caries and periodontal disease. In addition to it, effect in the healthy condition of oral mucosal surfaces. There are many systemic conditions (e.g., diabetes, cystic fibrosis) affect salivary flows, a patient complaining of dry mouth must be thoroughly investigated. These diseases may become severe after therapeutic irradiation in and around the mouth. The salivary gland become less active with age while is problematic, because such a great variation exists in the secretion of saliva, but no longitudinal studies have thus far been reported. Even so, histo-logical changes associated with age have been reported within the salivary glands. Fatty degenerative changes, fibrosis and the progressive accumulation of lymphocytes in the salivary glands are thought to occur. Oncocytes - epithelial cells that can be identified by there marked granularity and acidophilia under the light microscope, are thought to represent as age change, although their significance has not been established, beside accumulation of structurally altered mitochondria. Oncocytes are found in acini intercalated and striated ducts of salivary glands and which may give rise to neoplasms. The aim of this review is to provide athorough knowledge of anatomy, embryology and pathophysiology in ne-cessary to treat patient appropriately. Examines the cause, diagnostic methodology, radiographic evalu-ation and management of a variety of salivary gland.